2019
DOI: 10.35172/rvz.2019.v26.353
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Enterococcus faecium e Saccharomyces cerevisiae na resposta imunológica, parâmetros hematológicos e ganho de peso de bezerros alimentados com silagem de milho.

Abstract: O uso de probióticos a base de leveduras melhora o ganho de peso e o sistema imunológico de bovinos frente a grandes desafios imunológicos, no entanto permanece a dúvida se seu uso também apresentaria efeito em desafios mais tênues. Desta maneira, o presente trabalho verificou se o uso de probiótico a base de Enterococcus faecium e Saccaromyces cerevisiae via oral interfere na imunidade inata e no peso de bezerros sadios, em fase de crescimento, alimentados principalmente com silagem de milho. Para tanto, 12 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Oxidative metabolism was assessed by the colorimetric technique of reduction of nitroblue latrazolium (NBT), as described by Choi, Kim, Cha and Kim (2006), adapted by Flores et al (2019). For this, the blood was refrigerated until it was processed within a maximum of 3 h after harvest.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative metabolism was assessed by the colorimetric technique of reduction of nitroblue latrazolium (NBT), as described by Choi, Kim, Cha and Kim (2006), adapted by Flores et al (2019). For this, the blood was refrigerated until it was processed within a maximum of 3 h after harvest.…”
Section: Methodsmentioning
confidence: 99%
“…Londrina, v. 45, n. 2, p. 509-526, mar./abr. 2024 immunomodulation around 15 days after supplementation in calves (Flores et al, 2019;Bertagnon et al, 2024). Despite this, Villot el al.…”
Section: Althoughmentioning
confidence: 99%
“…Supplementation with the autolyzed yeast decreased the lasting and recurrence of diarrhea, as well as the fecal score of calves in the second and third weeks of the experiment. Our previous studies demonstrated that S cerivisiae supplementation promote an immunomodulation around 15 days after supplementation in calves(Flores et al, 2019;Bertagnon et al, 2024). Despite this, Villot el al.…”
mentioning
confidence: 94%
“…Saccharomyces cerevisiae é uma levedura benéfica aos animais, que pode ser usada com intuito de melhorar a performance digestiva e estimular a imunidade animal (Sanchez et al, 2014). Tem sido utilizada em suínos e aves com resultados expressivos na produtividade, o que motivou seu estudo em ruminantes seja em prol da produtividade como para aumentar a sanidade em geral (Flores et al, 2019;Sanchez et al, 2014). Saccharomyces cerevisiae pode ser usado como levedura íntegra, seja ela viva ou morta.…”
Section: Alternativa De Tratamento: Suplementação Com Saccharomyces C...unclassified